Text Messaging Improves HIV Care Continuum Outcomes Among Young Adult Trans Women Living with HIV: Text Me, Girl! - Reback, Cathy J.; Fletcher, Jesse B.; Kisler, Kimberly A. (AIDS & Behavior, 2021)
Young adult trans women living with HIV in the US exhibit suboptimal advancement through the HIV Care Continuum relative to national averages. From December 2016 through May 2018, 134 young adult trans women living with HIV enrolled in Text Me, Girl!, a theory-based, trans-specific text-messaging intervention designed to improve HIV Care Continuum outcomes. Participants (N = 130) averaged 29.5 years, were predominantly Latinx (43%) or African American/Black (40%). Clustered logistic and ordinal logistic multivariable models (n = 105; 366 observations) indicate that through 18-month follow-up, increased exposure to the text-messaging intervention was associated with significant (p < 0.05) increased retention to HIV care (adjusted odds ratio [aOR] 1.33) and biomarker-confirmed viral suppression (aOR 1.51); retention in the intervention was associated with significantly increased likelihood of ART uptake (aOR 2.95) and "excellent" ART adherence (aOR 10.44). Text Me, Girl! offers promising evidence that a unidirectional, automated text-messaging intervention can improve HIV care outcomes among young adult trans women living with HIV.